Pendampingan Penggunaan Teknologi Secara Bijak Kepada Anak Sekolah Dasar di Pesisir - Nahdatul Khairunisa; Martin Kustati; Gusmirawati Gusmirawati (Yayasan Keluarga Guru Mandiri, 2023)
Gadget is a technology that has a function to facilitate communication for humans. The advancement of gadget technology for the world of education also has a negative impact, which can cause students to be lazy to learn and play gadgets more often not on time. One of the activities is